Prevalence, predisposition and prevention of type II diabetes - Cheng Dong (Nutrition & Metabolism, 2005)
Abstract In 2000, more than 151 million people in the world are diabetic. It is predicted that by 2010, 221 million people and by 2025, 324 million will be diabetic. In the U.S., for the population born in 2000, the estimated lifetime risk for diabetes is more than 1 in 3. The economic and human cost of this disease is devastating. The current cost of diabetes in the U.S. is estimated to be at $132 billion, which includes $92 billion of direct medical costs and $40 billion of indirect costs such as disability, work loss and premature mortality. The outbreak of the current diabetic epidemic has been accompanied by a similarly drastic increase in obesity. The relation between the two is a matter of debate but presumably both are caused by changes in dietary habits and an increasingly sedentary modern lifestyle. Compelling scientific evidence indicates that lifestyle modification effectively prevents or delays the occurrence of type 2 diabetes. Recent clinical trials also demonstrate that success in the treatment of obesity, either surgically or pharmacologically, leads to the prevention of type 2 diabetes among the obese. Clinical data have also revealed that the insulin sensitizing agent troglitazone is efficacious in both β-cell preservation and delaying the onset of type 2 diabetes. Future safe and more effective anti-obesity medicines and insulin sensitizing agents that help to preserve β-cell function, in addition to efforts of lifestyle modification, thus hold promise for the overweight population with potential for reduction in the development of diabetics.